Epidemic urbanism : contagious diseases in global cities - Gharipour, Mohammad; DeClercq, Caitlin (Intellect Books Ltd, 2021)
The recent pandemic has put into perspective the impact of epidemic illness on urban life and exposed the vulnerabilities of societies. Interdisciplinary case studies from across the globe explore what insights from the outbreak, experience, and response to previous epidemics might inform our understanding of the current world. 150 b/w illus.